Estrogen‐inducible sFRP5 inhibits early B‐lymphopoiesis in vivo, but not during pregnancy. Issue 5 (16th March 2015) - Yokota, Takafumi; Oritani, Kenji; Sudo, Takao; Ishibashi, Tomohiko; Doi, Yukiko; Habuchi, Yoko; Ichii, Michiko; Fukushima, Kentaro; Okuzaki, Daisuke; Tomizuka, Kazuma; Yamawaki, Kengo; Kakitani, Makoto; et al.
<x xml:space="preserve">Abstract</x> Mammals have evolved to protect their offspring during early fetal development. Elaborated mechanisms induce tolerance in the maternal immune system for the fetus. Female hormones, mainly estrogen, play a role in suppressing maternal lymphopoiesis. However, the molecular mechanisms involved in the maternal immune tolerance are largely unknown. Here, we show that estrogen‐induced soluble Frizzled‐related proteins (sFRPs), and particularly sFRP5, suppress B‐lymphopoiesis in vivo in transgenic mice. Mice overexpressing sFRP5 had fewer B‐lymphocytes in the peripheral blood and spleen. High levels of sFRP5 inhibited early B‐cell differentiation in the bone marrow (BM), resulting in the accumulation of cells with a common lymphoid progenitor (CLP) phenotype. Conversely, sFRP5 deficiency reduced the number of hematopoietic stem cells (HSCs) and primitive lymphoid progenitors in the BM, particularly when estrogen was administered. Furthermore, a significant reduction in CLPs and B‐lineage‐committed progenitors was observed in the BM of sfrp5‐null pregnant females. We concluded that, although high sFRP5 expression inhibits B‐lymphopoiesis in vivo, physiologically, it contributes to the preservation of very primitive lymphopoietic progenitors, including HSCs, under high estrogen levels. Thus, sFRP5 regulates early lympho‐hematopoiesis in the maternal BM, but the maternal–fetal immune tolerance still involves other molecular mechanisms that remain to be uncovered.